Evidence on aggressors in cases of violence against older people: An integrative review - Alarcon, Miriam Fernanda Sanches; Damaceno, Daniela Garcia [UNESP]; Sponchiado, Viviane Boacnin Yoneda; Braccialli, Luzmarina Aparecida Doretto; Marin, Maria José Sanches (Revista Baiana de Enfermagem, 2019)
Objective: to identify evidence on aggressors in cases of violence against older people in national and international studies. Method: an integrative literature review was carried out in 2018 in the CINAHL, PubMed, Scopus, LILACS, Web of Science, and SciELO databases. The non-controlled descriptors (keywords) were: “Older people”, “Senior”, “Elderly”, and “Aggressor”. The controlled descriptors (Health Sciences Descriptors-DeCS) were: “Violence” and “Aged”. After close reading of 238 articles and 56 theses and dissertations, three articles and six dissertations and theses were selected. Results: a prevalence of the qualitative approach with low evidence level was found. The main aggressors found were older people’s children, who mostly reported repentance for their acts, which were often caused by alcohol and drug use, unemployment, history of family violence, closeness between aggressors and victims, and financial dependence on one of the parties. Conclusion: evidence on aggressors in cases of violence against older people in national and international studies was limited to their profile, type of violence practiced, and feelings regarding the act of violence.
EvidÊncias acerca do agressor em casos de violÊncia contra o idoso: RevisÃo integrativa
Evidencias sobre el agresor en casos de violencia contra el anciano: RevisiÓn integrativa
Keywords: Aged; Aggression; Older people